2007
DOI: 10.1002/jms.1362
|View full text |Cite
|
Sign up to set email alerts
|

An efficient method for dephosphorylation of phosphopeptides by cerium oxide

Abstract: In this article, an effective method for dephosphorylation of phosphopeptides by cerium oxide is described. The dephosphorylation activity of cerium oxide was evaluated by two standard phosphopeptides and the phosphopeptides in digests of phosphoprotein alpha-casein and beta-casein. Results showed that the dephosphorylation of all the phosphopeptides was completed in 10 min, and temperature had little effect on the dephosphorylation, the dephosphorylation could be carried out at 0 degrees C, room temperature a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
71
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(73 citation statements)
references
References 25 publications
0
71
1
1
Order By: Relevance
“…Interestingly, they observed that unlike the single nuclear complexes of cerium, the dephosphorylative activity of CeONP depends on the presence of Ce 3 þ sites and is inhibited when Ce 3 þ is converted to Ce 4 þ . This is contrary to the opinions of Qian and colleagues 68 who proposed a Ce 4 þ -mediated hydrolysis process. To fully understand the mechanism, additional research must be carried out.…”
Section: Nitric Oxide Radical Scavengingcontrasting
confidence: 81%
See 3 more Smart Citations
“…Interestingly, they observed that unlike the single nuclear complexes of cerium, the dephosphorylative activity of CeONP depends on the presence of Ce 3 þ sites and is inhibited when Ce 3 þ is converted to Ce 4 þ . This is contrary to the opinions of Qian and colleagues 68 who proposed a Ce 4 þ -mediated hydrolysis process. To fully understand the mechanism, additional research must be carried out.…”
Section: Nitric Oxide Radical Scavengingcontrasting
confidence: 81%
“…Third, temperature has little effect on the dephosphorylation; hence, precise control of the treatment temperature is not required, which facilitates the treatment process. 68 In a later study, Kuchma et al 34 reported that many biologically relevant molecules with phosphate ester, excluding DNA, could be hydrolyzed by CeONP. Interestingly, they observed that unlike the single nuclear complexes of cerium, the dephosphorylative activity of CeONP depends on the presence of Ce 3 þ sites and is inhibited when Ce 3 þ is converted to Ce 4 þ .…”
Section: Nitric Oxide Radical Scavengingmentioning
confidence: 99%
See 2 more Smart Citations
“…In this method, mass spectra of peptides before and after treatment with phosphatases were compared, and phosphopeptides were characterized as typical species presenting the unique mass shift owing to loss of 80 Da or n  80 Da. It is reported that ceria could efficiently mediate the dephosphorylation of phosphopeptides [28], and this ''solid phosphatase'' can be used as an alternative to alkaline phosphatase for dephosphorylation without introducing impurity. Therefore, we speculate that ceria-zirconia composites may not only provide good specificity for phosphopeptide, but also mediate the dephosphorylation of phosphopeptides.…”
Section: Introductionmentioning
confidence: 99%